Light and Strong SiC Networks. (5th February 2016) - Ferraro, Claudio; Garcia‐Tuñon, Esther; Rocha, Victoria G.; Barg, Suelen; Fariñas, Maria Dolores; Alvarez‐Arenas, Tomas E. Gomez; Sernicola, Giorgio; Giuliani, Finn; Saiz, Eduardo
Abstract : The directional freezing of microfiber suspensions is used to assemble highly porous (porosities ranging between 92% and 98%) SiC networks. These networks exhibit a unique hierarchical architecture in which thin layers with honeycomb‐like structure and internal strut length in the order of 1–10 μm in size are aligned with an interlayer spacing ranging between 15 and 50 μm. The resulting structures exhibit strengths (up to 3 MPa) and stiffness (up to 0.3 GPa) that are higher than aerogels of similar density and comparable to other ceramic microlattices fabricated by vapor deposition. Furthermore, this wet processing technique allows the fabrication of large‐size samples that are stable at high temperature, with acoustic impedance that can be manipulated over one order of magnitude (0.03–0.3 MRayl), electrically conductive and with very low thermal conductivity. The approach can be extended to other ceramic materials and opens new opportunities for the fabrication of ultralight structures with unique mechanical and functional properties in practical dimensions. Abstract : Ultralight SiC networks are assembled through the directional freezing of microfiber suspensions. The networks are stable at high temperature and have a unique hierarchical architecture that promotes high specific strengths and stiffness. They are thermally insulating but electrically conductive. The approach opens new opportunities for the fabrication of ultralight structures with unique mechanical and functional properties in practical dimensions.